2013
DOI: 10.1177/2050157913477095
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mobile phone use: Gender, age and real usage level in relation to the accuracy and validity of self-reported mobile phone use

Abstract: This article reports the results of a mobile phone use validation survey in which we compared self-reported mobile phone use to network provider data, and examined the observed discrepancies between both data sources in a convenience sample of 466 Flemish mobile phone users (18–65 years). The results showed significant discrepancies between self-reported and behavioral mobile phone use, particularly for the number and duration of mobile calls. Light users tended to overestimate, while heavy users tended to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 27 publications
8
57
2
Order By: Relevance
“…These findings correspond to previous research that has found low levels of measurement correspondence and tendencies of over-reporting for internet use (Scharkow, 2016). This pattern has also been found to apply for other media use behavior, such as the use of social media (Junco, 2013) or mobile phones (Vanden Abeele et al, 2013).…”
Section: Communication Methods and Measures 185supporting
confidence: 89%
See 2 more Smart Citations
“…These findings correspond to previous research that has found low levels of measurement correspondence and tendencies of over-reporting for internet use (Scharkow, 2016). This pattern has also been found to apply for other media use behavior, such as the use of social media (Junco, 2013) or mobile phones (Vanden Abeele et al, 2013).…”
Section: Communication Methods and Measures 185supporting
confidence: 89%
“…Particularly, those with higher levels of actual internet use as well as tablet users showed lower levels of over-reporting and, accordingly, higher levels of under-reporting and, thus, clearly deviated from the general tendencies of over-reporting. Related to this point and also in line with previous findings, the variance in the self-reported measures was smaller compared to the actual behavior which could imply a lower explanatory power of self-reported measures of internet use (Scharkow, 2016;Vanden Abeele et al, 2013;Wonneberger & Irazoqui, 2016). Corroborating these previous studies, actual internet use was identified as a main driver for this phenomenon: Greater levels of internet use were associated to higher levels of underreporting and lower levels of internet use to higher levels of over-reporting.…”
Section: No Differencessupporting
confidence: 87%
See 1 more Smart Citation
“…First, subjective self-reports of usage intensities of SMS and MI services in general or IP-based mobile instant messaging applications in particular share very limited variance with objective behavioral data derived from traffic measurement or billing systems of MNO or software clients installed on smartphones to capture customer service use patterns (Van den Abeele et al, 2013;Boase and Ling, 2013;Gerpott, 2011;. Thus, self-assessments of use intensities of mobile communication services' inaccurately reflect actual customer behaviors.…”
Section: Conceptual Background and Research Questionsmentioning
confidence: 96%
“…Previous work has shown significant differences between the self-responses of research participants and their actual behaviour, especially in the number and duration of mobile calls (Vanden Abeele, Beullens, & Roe, 2013). Other studies have also shown that due to the large number of applications that the user may have installed, the user may find it difficult to enumerate all the installed applications and their daily use (Xu et al, 2016), thereby ruling out the possibility of introducing biases of answers by social desirability.…”
Section: Data Collection and Measuresmentioning
confidence: 99%